The Urgency Of Providing Restitutions For Victims Of Sexual Violence - Itok Dwi Kurniawan (Islamic Research Publiser, 2023)
Criminal acts of sexual violence are crimes that are rife in Indonesia today. Most of the existing laws and regulations in Indonesia only focus on punishment for perpetrators of sexual violence crimes. Meanwhile, victims of sexual violence have not received proper attention, especially with regard to compensation for the losses they have experienced. This article aims to examine the laws and regulations governing the provision of restitution for victims of sexual violence and the problems encountered in providing restitution for victims of sexual violence. The results of this study indicate that granting restitution to victims of sexual violence can be submitted to the Witness and Victim Protection Agency, and the problem in the practice of granting restitution to victims of sexual violence is the lack of government support to provide restitution rights for victims, and not yet there are coercive measures and sanctions against perpetrators of crimes against victims of sexual violence that do not provide restitution.